NEW RECORDS AND ICHNOSPECIES OF LINEAR LEAF MINES FROM THE LATE MIOCENE-PLIOCENE FROM ARGENTINA AND THE ESTABLISHMENT OF LEAF-MINING ICHNOTAXOBASES (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2016)
The ichnospecies Cuniculonomus parallelus Givulescu 1984 and Stigmellites serpentina Kozlov 1988 are recorded for the first time in Argentina and the new ichnospecies Cuniculonomus saltensis isp. nov., Stigmellites vitatus isp. nov. and Stigmellites pervenae isp. nov are defined from two Miocene localities: Peñas Blancas and Quebrada del Horno, from northwestern Argentina. A set of characters to identify fossil linear mines is provided as well as five ichnotaxobases to differentiate the ichnogenera Cuniculonomus, Stigmellites and Phytomyzites. Two ichnospecies are now revised and included in Phytomyzites: P. arcuata (Krassilov 2008a) comb. nov. (Ophionoma) and P. crucitracta (Krassilov 2008a) comb. nov. (Troponoma). Finally, a review of fossil record of linear mines is provided.